Penerapan Model Meaningful Learning untuk Meningkatkan Hasil Belajar Siswa - Khoirussaadah Khoirussaadah; Wahyu Prihatiningrum; Wahyu Prakosa; Agung Yulianthoro; Haniah Budiastuti; Siti Rokhimah (Kampus Akademik Publiser, 2025)
The measurement of learning outcomes is the main indicator in assessing the effectiveness of learning methods in the classroom, because learning outcomes reflect academic achievement as well as the level of understanding and ability of students after participating in the learning process. One of the learning models that can improve student understanding is the Meaningful Learning model. This research aims to describe the implementation steps, advantages, and disadvantages of Meaningful Learning model in learning at Madrasah Aliyah Negeri 2 Rembang, Madrasah Tsanawiyah Negeri 4 Klaten, Madrasah Aliyah Negeri 1 Kebumen, and Madrasah Aliyah Negeri 3 Boyolali, dan Madrasah Tsanawiyah Negeri 3 Sukoharjo. The research method used a qualitative approach with the research subjects being teachers, while the data collection techniques were conducted through interviews, observations, and documentation. The results showed that the steps of Meaningful Learning include: determining learning objectives, identifying student characteristics, compiling material according to these characteristics in the form of core concepts, presenting topics with advance organizers, learning core concepts and applying them concretely, and assessing the process and learning outcomes. This model has advantages, such as increasing long-term retention, facilitating knowledge transfer, encouraging learning motivation because students feel they are learning something meaningful, and developing critical and creative thinking skills. However, the disadvantage is that teachers often have difficulty determining concrete examples and study groups tend to depend on smarter students. In conclusion, Meaningful Learning can be applied to improve student learning outcomes in madrasah.